2003
DOI: 10.1177/002215540305100707
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Collagen XVII Expression During Transformation of Oral Epithelium to Dysplasia and Carcinoma

Abstract: (LB-T)S U M M A R Y Collagen XVII (BP180) is a hemidesmosomal transmembrane component that has been hypothesized to participate in keratinocyte adhesion and motility. Using immunohistochemical (IHC) and in situ hybridization (ISH) methods, we showed downregulation of collagen XVII in basal cells in mild dysplasias and upregulation in suprabasal keratinocytes in moderate and severe dysplasias as well as in the central cells of grade II and III squamous cell carcinomas (SCCs). Overexpression of collagen XVII was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 32 publications
(47 reference statements)
4
52
0
Order By: Relevance
“…Here, we have provided evidence that Col XVII, by mediating the association of BPAG1e and ␣6␤4 integrin, is an important regulator of the keratinocyte lamellipodium, the key organelle that generates the force necessary for directional protrusion at the cell periphery (49,53). Thus, our results now provide a critical new understanding of the consequences of up-regulation of Col XVII, ␣6␤4 integrin, and BPAG1e in aggressive tumors and the presence of these proteins at the leading front of migrating tumor and epidermal cells covering wounds (17,20,(42)(43)(44)(45). They are clearly key players in the regulation of motility.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Here, we have provided evidence that Col XVII, by mediating the association of BPAG1e and ␣6␤4 integrin, is an important regulator of the keratinocyte lamellipodium, the key organelle that generates the force necessary for directional protrusion at the cell periphery (49,53). Thus, our results now provide a critical new understanding of the consequences of up-regulation of Col XVII, ␣6␤4 integrin, and BPAG1e in aggressive tumors and the presence of these proteins at the leading front of migrating tumor and epidermal cells covering wounds (17,20,(42)(43)(44)(45). They are clearly key players in the regulation of motility.…”
Section: Discussionsupporting
confidence: 54%
“…For example, we and others have demonstrated that ␣6␤4 integrin is directly involved in regulating signals that control motile phenomena (16,18,19,21,41). Moreover, the up-regulation of ␣6␤4 integrin, BPAG1e, and Col XVII in aggressive tumor cells, their presence in lamellipodia in cultured cells, and the observation that they are found in the leading edge of cells populating wounds point to a more direct role in migration (17,20,(42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 85%
“…Collagen XVII is mutated in epidermolysis bullosa, is a serum antigen in a number of skin blistering conditions (reviewed in ref. 26), and is up-regulated in oral and squamous basal cell carcinomas (27,28). Collagen XIII is a serum antigen in the autoimmune disease, Graves' ophthalmopathy (29), and was recently reported to be up-regulated in mesenchymal tumors and in the stroma of epithelial tumors (30), whereas collagen XXV is deposited in Alzheimer's plaques (31).…”
Section: Discussionmentioning
confidence: 99%
“…In light of this, the evidence that altered expression of desmosomal proteins in various human malignancies has been accumulating. [175].…”
Section: Malignancy In Relation To the Autoimmunity In Pemphigus Groumentioning
confidence: 99%